Generation of multi-carrier based on a recirculating frequency shifter with delay interferometer - 成虹桥 席丽霞 林嘉川 张晓光 张霞 李建蕊 (Optoelectronics letters, 2013)
Recirculating frequency shifter （RFS） can generate stable multi-carder, but the carder-to-noise-ratio （CNR） is limited because noise is accumulated round by round in the recirculation loop structure. A modified RFS with a delay inter- ferometer （DI） is proposed in this paper. The DI can suppress the accumulated noise, and enhance the CNR of multi-carrier. The principle of the generation of high quality multi-carrier based on an RFS with DI is analyzed theoretically. 50 stable carriers with spacing of 10.7 GHz are successfully generated. The flatness of 50 stable carriers is 3 dB, and the CNR is 43 dB which is increased by 3 dB compared with the structure without DI.